Avaliação da disautonomia na doença de Parkinson - Silva, Bruna Nadiely Victor da (2021)
The symptoms of dysautonomia are frequent non-motor complaints in Parkinson’s disease (PD). They are present even in the early stages of disease and cause a negative impacto in quality of life. The aim of study was: to chacaterize the dysautonomy profile of individuals with PD treated at University Hospital Lauro Wanderley; to make comparisions between groups of patients, which were segregated by the modified Hoen-Yarh score, time of disease and total daily levodopa dose. Twenty subjects participated in the research, who underwent a neurological clinical evaluation, application of a socio-demographic questionnaire, modified Hoen-Yarh and SCOPA-AUT. Data were evaluated through SPSS, using the Mann-Whitney test, considering the level of significancfe p < 0.05. The most frequent symptom of dysautonomy was nocturia (90%). The most affected domains were: urinary and gastrointestinal, with 100% of participants reporting at least one symptom of each, with the majority having 04 affected domains (45%). The average amount of symptoms presente was 11.05 (4-17, standard deviation 0.94). The average SCOPA-AUT score was 21.85 (6-40, standard deviation of 9.06). The comparison between groups, according to the modified Hoen-Yarh score, showed a significant difference between groups with scores up to 2,0 and from 2,5 only for the daily total levodopa (U = 22.5, z = -2.06, p = 0.047). There was no statistical significant difference for the variables: age, time of disease and SCOPA-AUT score. There were significant diferences between groups (levodopa dose ≤ 400mg and > 400 mg) for orthostatic symptoms (U = 21, z = -2.189, p = 0.039); gastrointestinal (U = 13.5, z = -2.731, p = 0.012). Autonomic dysfunction is a clinically relevant and widespread problem in PD, wich it can be presente even in early stages, and don´t have a defined pattern of involvement. And so, it’s necessary to research and properly treat these non-dopaminergic symptoms throughot the course of the disease, providing improvement in quality of life.